CLIMATOLOGIES OF OZONE AND UV-B IRRADIANCES OVER ANTARCTICA IN THE LAST DECADES - Diaz,Susana B (Facultad de Ciencias Naturales y Oceanográficas, Universidad de Concepción, 2004)
Antarctica is the continent that has suffered the strongest variations in total ozone column and UV-B radiation, during the last decades, as consequence of the "ozone hole". Systematic measurements of total ozone column are being performed since the late 1950s at ground stations, and global coverage is available since the late 1970s, with measurements provided by instruments installed at different satellites (Nimbus-7, Meteor-3, Adeos, Earth-Probe, Gome). In 1988, the National Science Foundation (US) initiated the activities of the NSF UV Radiation Monitoring Network, installing three spectro-radiometers SUV-100/BSI in South Pole, Mc Murdo and Palmer Stations, and one in Ushuaia. Now, a time series of more than ten years is available for all stations. Nevertheless, there are no records of background spectral irradiances, prior to the "ozone hole". Then, we completed the databases, for South Pole, dating back to the late 1970´s, with narrow-band and biologically weighted irradiances inferred, applying a multi-regressive model, from total ozone column and pyranometer data from the NOAA/CMDL surface radiation budget database. Combining the above-mentioned databases, we will present a discussion on the climatologies of ozone and irradiances over Antarctica, in the last decades